2003
DOI: 10.1071/as02031
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetry of GPS and CSS Sources

Abstract: Abstract:The role of radio polarimetry in the understanding of GPS and CSS sources is explored. After an initial discussion of what can be learned from polarimetry, the expectations of a simple evolutionary sequence of GPS/CSO to CSS to FR i/FR ii sources are explored. Observational results are then compared with the expectations. Conclusions include: the GPS category is likely not a single homogeneous class of objects; Faraday depth effects are very strong inside the inner 3 kpc of CSS and CSO sources; in at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 12 publications
7
42
3
Order By: Relevance
“…Figure 2.7: Fractional polarization at 1.4 GHz plotted versus the frequency of the peak in the spectrum for a GPS sample (Cotton et al, 2003). This is consistent with the picture of a small radio source with normal polarization properties whose radio emission is subject to severe Faraday rotation with inhomogeneities on very small scales, producing depolarization.…”
Section: Polarizationsupporting
confidence: 65%
See 2 more Smart Citations
“…Figure 2.7: Fractional polarization at 1.4 GHz plotted versus the frequency of the peak in the spectrum for a GPS sample (Cotton et al, 2003). This is consistent with the picture of a small radio source with normal polarization properties whose radio emission is subject to severe Faraday rotation with inhomogeneities on very small scales, producing depolarization.…”
Section: Polarizationsupporting
confidence: 65%
“…Such ISM may be responsible for the lack of polarization. Cotton et al (2003) found that small radio sources are unpolarized in the NVSS at 1.4 GHz ( Fig. 2.7), while at higher frequencies sources with size of about a few kpc start to show some fractional polarization at progressively smaller projected linear sizes (Fanti et al, 2004).…”
Section: Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fanti et al (2001) found that in the B3-VLA sample a large fraction of MSOs are polarized at 4.9 and 8.4 GHz, while CSOs mostly aren't. This was further strengthened by Cotton et al (2003c) with www.an-journal.org the plot reported in Fig. 5, obtained at 1.4 GHz from the NVSS (Cotton effect).…”
Section: Statistical Results: Fractional Polarization (M λ )mentioning
confidence: 99%
“…This turns out in very low fractional polarization limits on the brightest features (hot spots), typically less than 0.5-1% depending on the peak brightness; the upper limit on the low surface brightest regions increases to 10-20%. If the very low level of polarization is due to an external Faraday screen (see Fanti et al 2004, Paper IV, for a Faraday screen model, and also Cotton et al 2003) the screen coherence length is required to be smaller than a few parsecs.…”
Section: Polarization Propertiesmentioning
confidence: 99%